Датчик віброшвидкості з функціями контролю і аналізу вібраційних параметрів енергообладнання - Шульженко, Микола Григорович; Єфремов, Юрій Геннадійович; Депарма, Олександр Вадимович; Цибулько, Вадим Йосипович (НТУ "ХПІ", 2017)
Для вимірювання параметрів вібрації елементів енергетичного обладнання пропонуються датчики віброшвидкості з цифровою обробкою сигналу. Датчик визначає спектральні складові та середньоквадратичні значення віброшвидкості у заданих смугах частот вимірювання, сигналізує про перевищення середньоквадратичних значень віброшвидкості заданих рівнів та про різку зміну (стрибок) вібрації. Датчики використано для оцінки вібраційного стану турбоагрегата К-300-240.

A reliability of the assessment of the vibration state of the units depends to a certain extent on the accuracy and reliability of technologies and the software used for the control and measurement of vibration parameters. Developing vibration rate sensors that provide in full the appropriate level of metrological and operating performances in the real time mode is an important scientific and engineering problem and the actuality of it is defined by the requirements set to the sensors of a new generation. An intelligent vibration rate sensor was developed using the state-of-the-art element base with the microcontroller of an STM32 type to assess the vibration state of nonrotating parts of the equipment. The sensor has a contact eddy current primary transducer and a functional transducer to process signals. The sensor software has the functions that compensate the influence of temperature and nonlinearity of the amplitude-frequency characteristic of primary transducer, automatic adjustment of the amplitude range for the measurement of the root-mean-square value of vibration rate and automatic trouble-shooting test function in the case of improper functioning. This sensor allowed us to get spectral characteristics of the vibration rate for turbounit supports.
Vibration rate sensor with the power equipment vibration parameter control and analysis functions
Keywords: перетворювач вихрострумовий; мікроконтролер; вібрація; віброшвидкість; спектр; турбоагрегат; eddy current transducer; microcontroller; vibration; vibration rate; spectrum; turbounit